Hubungan Pengetahuan dan Sikap Ibu Hamil dengan Perilaku Pencegahan Covid–19 dalam Adaptasi Kebiasaan Baru - Fauziah, Nur Alfi; Yuliasari, Riting; Febriyanti, Hellen (Journal of Research in Social Science and Humanities, 2021)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by SARS-CoV-2. Based on data from the Lampung Provincial Health Office (2020), four patients who are pregnant have been confirmed positive for COVID-19. At Gilang Tunggal Makarta Public Health Center of West Tulangbawang Regency (2020) there is 1 pregnant woman aged 22 years old and who has a history of having travelled from DKI Jakarta to be confirmed positive for COVID-19. The purpose of this research is to know the correlation between knowledge and pregnant women attitudes with covid-19 prevention behaviours on new habits adaptation in the working area of Gilang Tunggal Makarta Public Health Center West TulangBawang Regency in 2021. This type of research is quantitative by applying an analytic research design with a cross-sectional approach, the population is all pregnant women as many as 34 people, the total sample size from the population. Univariate data analysis used a percentage frequency distribution and bivariate used the chi-square test. The research result showed that the frequency distribution of pregnant women knowledge was higher in the unfavourable category as many 20 people (58.8%), the pregnant women attitude were higher in the negative category as many as 19 people (55.9%) and the prevention behaviour of COVID-19 was higher in the unfavourable category amounted to 21 people (61.8%). The results of the chi-square test showed a correlation between knowledge (p-value = 0.000 0.05) and behavior (p-value = 0.001 0.05) with COVID-19 prevention behavior on new habits adaptation. It is hoped that health workers will be more active in socializing COVID-19 prevention behaviour through direct counselling on demonstration methods accompanied by discussion using leaflets or brochures using interesting pictures and writing also using simple language.